Optimal auctions for asymmetrically budget contrained bidders - Alexey Malakhov; Rakesh V. Vohra (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2005)
We consider an environment with a single divisible good and two bidders. The valuations of the bidders are private information but one bidder has a commonly known budget constraint. For this environment we derive the revenue maximizing subsidy free incentive compatible auction. We also examine the case when the budget constraint is private information but bidders must post a bond.
Keywords: 330; Auktionstheorie; Asymmetrische Information; Budgetrestriktion; Theorie